Effect of Extraction Method on Yellow Wood Rendement and Phenolic Content (Arcangelisia flava (L.) Merr) UV-Vis Spectrophotometry Extract of Ethanol - Sasnita, Merida; Daulay, Anny Sartika; Ridwanto, Ridwanto; Nasution, Haris Munandar (Pustaka Media Publishing, 2023)
Indonesia is a country rich in biodiversity. With the wealth of natural resources, there is very much that can be used from flora and fauna to treat various diseases, yellow wood is one of the plants that have medicinal properties and has not been widely studied, yellow wood is efficacious as antimicrobial, antioxidant, antihyperlipidemia, and anticancer. The objective of this study was to determine the class of chemical compounds found in simplicial and extracts of yellow wood plants and to determine the effect of extraction methods on the yield and phenolic levels of ethanol extracts of yellow wood plants. The stages of this research include processing plant materials, making maceration extracts and socletation of yellowwood plants, examination of characteristics, phytochemical screening and determination of total phenolic levels of ethanol extract 96% maceration and socleation of yellow wood (Arcangelisia flava (L.) Merr) by UV-Vis Spectrophotometry method. The highest yield research results are found in the maceration extract yield, this is because the maceration process time is shorter than the socleation process, so that the compound withdrawal process carried out by maceration is more optimal than the socleation method. In addition, the more solvent used, the more extracts produced. The determination of total phenolics is performed by determining the maximum wavelength of gallic acid using UV-Vis spectrophotometry methods. Yellowwood maceration ethanol extract has a total phenolic content of 22.0087 ± 0.8567 mg GAE/g and socleation extract has a total phenolic content of 18.2023 ± 0.1434 mg GAE/g.